Naloxone urban legends and the opioid crisis: what is the role of public health? - Alexis Crabtree; Jeffrey R. Masuda (BMC, 2019)
Abstract As the overdose crisis in North America continues to deepen, public health leaders find themselves responding to sensational media stories, many of which carry forms and themes that mark them as urban legends. This article analyzes one set of media accounts - stories of misuse of naloxone, an opioid overdose antidote distributed to people who use drugs - through the lens of social science scholarship on urban legends. We suggest that these stories have met a public need to feel a sense of safety in uncertain times, but function to reinforce societal views of people who use drugs as undeserving of support and resources. Our field has a duty to speak out in favour of evidence-based programs that support the health of people who use drugs, but the optimal communication strategies are not always clear. Drawing attention to the functions and consequences of urban legends can help frame public health communication in a way that responds to needs without reinforcing prejudices, with application beyond naloxone to the other urban legends that continue to emerge in response to this crisis.